Decision and coordination of WEEE closed-loop supply chain with risk aversion under the cap-and-trade regulation - Zhou F.; Zhang C.; Tiwari S.; Huang X.; Pratap S. (My University, 2025)
Driven by the soaring consumption of electrical and electronic equipment (EEE), the semiconductor industry is facing sustainable development challenges such as energy management and carbon emissions. The waste electrical and electronic equipment (WEEE) management practice could contribute to achieving sustainability in the semiconductor industry through the remanufacturing business. Considering the collection quality heterogeneity and its potential influences on the WEEE remanufacturing process, this paper tries to explore the decision-making strategy and coordination mechanism of the WEEE closed-loop supply chain (CLSC) under the cap-and-trade regulation (CATR). The Stackelberg game model is formulated to address this context consisting of a manufacturer with risk avoidance and a retailer with risk neutrality. Besides, we disclose the specific influence of WEEE collection quality on the strategic decision-making of CLSC members under decentralized and centralized modes. Additionally, the revenue and cost-sharing contract is designed to facilitate coordination within the CLSC, and numerical experiments are performed to help better understand the strategic decision-making and effectiveness of the designed contract mechanism. Results show that within a certain threshold of WEEE collection quality, both recycling rate and total profit increase as collection quality improves, while unit wholesale and retail prices of EEE decrease. Conversely, as the risk aversion of the manufacturer increases, the return rate of WEEE decreases, while the wholesale price and retail price per unit of EEE rise. Under the joint influence of the unit carbon emission quota trading price and risk aversion, the unit carbon emission quota trading price exacerbates the impact of manufacturer risk aversion on the return rate. The revenue and cost-sharing contract also contributes to achieving WEEE CLSC coordination under specific conditions. © 2024 Elsevier B.V.